The proposition that x = v t leads to a contradiction with Special Relativity - Suleiman, Ramzi (JOURNAL OF ADVANCES IN PHYSICS, 2014)
This short note posits the indisputable physical law prescribing that distance = velocity x time, and shows that this proposition contradicts Special Relativity, such that the above proposition is correct and Special Relativity is incorrect, or vice versa.